Upaya Pemerintah Desa dalam Pengembangan Ekonomi Lokal melalui Desa Wisata : Studi di Desa Lubuk Beringin Kabupaten Bungo - Siti Mulyati; Supardal Supardal (CV. Ulil Albab Corp, 2023)
This research was conducted with the aim of knowing how the village government's efforts in developing tourism in lubuk beringin village and conducted for the purpose of knowing what are the inhibiting factors of the village government in developing lubuk beringin tourism village. Local economic development is a process of community participation, local government, and the private sector to increase competitiveness through existing resources with the aim of creating decent work. Through tourism development, it is expected that equalization can occur in accordance with the concept of tourism development. Local communities play an important role in tourism development because of the resources and uniqueness of traditions and culture that exist in the village. This research uses a descriptive qualitative method with phenomenological approach. This research uses the theory of Pitana and Gayatri (2005) which has 3 components, namely; facilitator, motivator, and dynamizer. The object of research is local economic development in lubuk beringin village. Data collection techniques were carried out by means of observation, interviews, and documentation. The findings of the results of this study are the efforts of the Village Government in developing the local economy with indicators that have been determined to be appropriate, such as infrastructure, and infrastructure, but there is still a slight lack such as road access that has not been repaired so that it can be said that it is not optimal. Thusthere are also inhibiting factors, namely; lack of infrastructure and road access to the village which still has many holes and has not been properly managed, low human resources and community participation in the development of tourism.